Changes in Organic Matter Deposition Can Impact Benthic Marine Meiofauna in Karst Subterranean Estuaries - Brankovits, David; Little, Shawna N.; Winkler, Tyler S.; Tamalavage, Anne E.; Mejía-Ortíz, Luis M.; Maupin, Christopher R.; Yáñez-Mendoza, German; van Hengstum, Peter J. (Frontiers in Environmental Science, 2021)
Subsurface mixing of seawater and terrestrial-borne meteoric waters on carbonate landscapes creates karst subterranean estuaries, an area of the coastal aquifer with poorly understood carbon cycling, ecosystem functioning, and impact on submarine groundwater discharge. Caves in karst platforms facilitate water and material exchange between the marine and terrestrial environments, and their internal sedimentation patterns document long-term environmental change. Sediment records from a flooded coastal cave in Cozumel Island (Mexico) documents decreasing terrestrial organic matter (OM) deposition within the karst subterranean estuary over the last ~1000 years, with older sediment likely exported out of the cave by intense storm events. While stable carbon isotopic values (δ13Corg ranging from −22.5‰ to −27.1‰) and C:N ratios (ranging from 9.9 to 18.9) indicate that mangrove and other terrestrial detritus surrounding an inland sinkhole are the primarily sedimentary OM supply, an upcore decrease in bulk OM and enrichment of δ13Corg values are observed. These patterns suggest that a reduction in the local mangrove habitat decreased the terrestrial particulate OM input to the cave over time. The benthic foraminiferal community in basal core sediment have higher proportions of infaunal taxa (i.e., Bolivina) and Ammonia, and assemblages shifted to increased miliolids and less infaunal taxa at the core-tops. The combined results suggest that a decrease in terrestrial OM through time had a concomitant impact on benthic meiofaunal habitats, potentially by impacting dissolved oxygen availability at the microhabitat scale or resource partitioning by foraminifera. The evidence presented here indicates that landscape and watershed level changes can impact ecosystem functioning within adjacent subterranean estuaries.